2013
DOI: 10.3389/fpsyg.2013.00957
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanisms of action understanding in left and right-handed subjects: the role of perspective and handedness

Abstract: The ability to comprehend outcomes of skilled action is important for understanding the world around us. Prior studies have evaluated the perspective an action is performed in, but few have evaluated how handedness of the actor and the observer interact with action perspective. Understanding handedness affords the opportunity to identify the role of mirroring and matched limb action encoding, which may display unique strategies of action understanding. Right and left-handed subjects were presented with images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
4
5
0
Order By: Relevance
“…This contradicts previous studies by [27,67] which both showed improved learning with congruent handedness. Our study is, instead, consistent with the results of [58] that handedness congruence had no effect on performance in a tool action prediction task. Our findings are also in line with [60], who suggest that handedness does not affect object representations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This contradicts previous studies by [27,67] which both showed improved learning with congruent handedness. Our study is, instead, consistent with the results of [58] that handedness congruence had no effect on performance in a tool action prediction task. Our findings are also in line with [60], who suggest that handedness does not affect object representations.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, visual object recognition is affected by the object's orientation [56,57]. People are better at action prediction for images of tools viewed from the perspective that they would see when using them [58]. Furthermore, in haptic (active touch) tasks, recognition is easier when objects are explored from the orientation typically used to manipulate them ( [59], but see [60]).…”
Section: Introductionmentioning
confidence: 99%
“…[31/36]) felt as if they were performing the nursing skill while seeing the VR-TM (rating > +1). Actually, previous studies in cognitive science reported that the first-person perspective facilitates visuomotor information processing and motor planning compared to the third-person perspective [6] [7]. Given these findings, it appears that observing the first-person video via the HMD enhanced the visuomotor processes in this study.…”
Section: Discussionsupporting
confidence: 55%
“…It is also known that perspective of action may impact the action observation system and subsequent behavioral outcomes (Saxe et al, 2006;Kelly and Wheaton, 2013). It is possible that varying the perspective may substantially affect action observation training.…”
Section: 0 Introductionmentioning
confidence: 99%